In-situ measurement of structural performance of large-span air-supported dome under wind loads. (December 2021) - Yin, Yue; Chen, Wujun; Hu, Jianhui; Zhao, Bing; Wang, Qin
Abstract: To comprehensively understand the wind-induced response of air-supported membrane structure, a structural health monitoring system is designed and firstly installed on a pneumatic membrane sports hall with large span. Consisting of four sub-systems, this system was applied to perform a long-term in-situ monitoring. Structural vibration data of outer fabric membrane and steel cable tension strain were acquired during the passage of typhoon Lekima in 2019, as well as internal pressure and wind pressure posed on the structure. Natural frequency and damping ratio are identified based on acceleration data. First five modes are obtained with natural frequencies ranged from 0.279 Hz to 0.457 Hz. Damping ratios approximates 1.5%. Modal shapes are mainly along with lateral and vertical directions. Besides, monitoring results show that the internal pressure of the pneumatic sports hall slightly fluctuates with the structural geometry variation induced by external wind. Windward pressure and wind suction at roof top are primary factors affecting the deformation of outer fabric membrane and cable strain. Specifically, with wind intensity increasing the structure geometry changes from semispherical to conical shape in side view and is twisted by the moment induced via wind load. It is also found that cables at roof ridge area have larger strain than those close to roof edges. Highlights: An in-situ measurement of the wind-induced response of air-supported structure is firstly performed by comprehensive structural health monitoring system. The effects of wind load on membrane deformation and steel cable strain are analyzed. Natural frequencies, damping ratios and modal shapes of air-supported structure are calculated.